Florida Container Mosquitoes - L. Philip Lounibos; Eva A. Buckner (EDIS)
Container mosquitoes inhabit small natural and artificial water-filled vessels during their immature stages. This publication lists and illustrates fifteen species of them, including two exotics that are the most important vector species of dengue, chikungunya, yellow fever, and Zika viruses. It also describes available control measures, the best for homeowners being to eliminate aquatic habitat by draining standing water in containers near homes.